Pengembangan Multimedia Pembelajaran Interaktif untuk Mata Pelajaran Matematika untuk Kelas 5 Sekolah Dasar - Firmansyah, Feri Hidayatullah; Fajriyah Aldriani, Sekar Nurul; Dewi, Elsya Roziana (Universitas Pendidikan Indonesia (UPI), 2020)
The learning process during a pandemic requires teachers to be more interactive in making online learning media. The government has designed the Covid Emergency Curriculum, which is that educational units in their current condition can choose one of the several components needed in the learning process, namely still referring to the national curriculum, using the emergency curriculum, or making curriculum simplification independently. For curriculum simplification, only the main material in learning activities needs to be conveyed, while for practice it can be independently or through an application media. This study aims to create an augmented reality-based learning media on geometry in mathematics subjects for grade 5 elementary school. This media can make it easier for students to understand the shapes with augmented reality and there is a learning video feature that also explains the material presented by the teacher. With the black box white box method, the application is developed by adjusting the curriculum simplification planned by the government. Features in the application include objectives and materials, learning videos, augmented reality simulations and integrated with Google Classroom as a learning evaluation platform. The results of this research are digital applications that can be accessed from the web or android applications.